Maximum River Runoff in Poland Under Climate Warming Conditions - Brzezińska Wiktoria; Wrzesiński Dariusz (Quaestiones Geographicae)
The aim of the study was to investigate the trends of changes in maximum daily river discharge in Poland from 1951 to 2020 under climate warming conditions. The study covered two sub-periods: 1951–1988 and 1988–2020, with 1988 considered the conventional year for the change in thermal conditions. Daily maximum discharge was calculated using data from 148 water gauge stations located on 97 rivers, and the Mann-Kendall test was used to analyse trends. The results showed the prevailing falling trends (more than 85%) on the rivers of central and eastern Poland, 40% of which were of statistical significance (p<0.05). The lowest discharge increased on more than 58% of the profiles, 27% of which were of statistical significance (p<0.05). The most common falling trends in maximum discharge were observed in spring (87% of the profiles) and summer (77%), with statistically significant changes accounting for 37% and 22%, respectively. Increases were recorded mainly in autumn on rivers in southern Poland and in winter – in the north-eastern part of the country. In the period after 1988, maximum discharge decreased in most seasons, especially in summer, where in August discharge decreased by as much as more than 50% in central Poland, with significant changes affecting 30% of profiles. The effect of climate warming on extreme discharge was clearly spatially differentiated, especially in spring and summer in central and eastern Poland.